SUNDA'S LOCAL ASSISTANCE IN LEADERSHIP - Ika Sri Hastuti; Kunkunrat Kunkunrat; Ade Priangani; Rasman Sonjaya (SAMPURASUN, 2021)
Sundanese local wisdom is the values ​​resulting from the wisdom of the Sundanese people in carrying out their lives as people, rishis and kings. The kings of Sundanese at that time in leading were guided by the characteristics a leader must have written in the ancient Sanghyang Siksakandang Karesian script. Method using the literature review method by analyzing the literature on Sundanese leadership in the past and in the present. The results of data analysis from several journals discuss Sundanese local wisdom in leadership issues based on the ancient Siksakandang Karesian text, which explains that Sundanese leadership is guided by parigeuing. The figure of an ideal leader must stick to the astaguna principle of "eight wisdoms", so that his leadership is harmonious, good, and harmonious. The eight wisdoms as stated by Darsa (1998) are as follows: Animan (gentle), Ahiman (firm), Mahiman (broad-minded, Lagiman (agile / nimble / skilled), Prapti (right on target), Prakamya (tenacious / diligent) , Isitwa (honest), Wasitwa (open to criticism) This Sundanese leadership figure has weaknesses, because openness and admiration are one of the obstacles that make it difficult for Sundanese people to compete at the national level with Javanese ethnicities. Keywords: Local Wisdom, Leadership, Sundanese